2018
DOI: 10.1021/acs.jafc.8b05793
|View full text |Cite
|
Sign up to set email alerts
|

Imidacloprid Impacts on Neurobehavioral Performance, Oxidative Stress, and Apoptotic Events in the Brain of Adolescent and Adult Rats

Abstract: Currently, imidacloprid (IMI) is the first insecticide and the second agrochemical highly applied all over the world. Here, we report on the impacts of IMI on neurobehavioral performance, oxidative stress, and apoptotic changes in the brain in either adult or adolescent rats. Forty male rats (adult and adolescent) were allocated to four groups. IMI groups were orally given 1 mg IMI/kg b.wt. dissolved in corn oil, whereas the controls were orally administered corn oil daily for 60 days. The obtained results dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 72 publications
7
36
0
Order By: Relevance
“…The results of GABA showed that IMI exposure caused a significant decrease in GABA level. These results agree with that obtained by Abd-Elhakim et al [28]. Administration of GAE simultaneously with IMI modifies the release of some neurotransmitters particularly GABA [29].…”
Section: Discussionsupporting
confidence: 93%
“…The results of GABA showed that IMI exposure caused a significant decrease in GABA level. These results agree with that obtained by Abd-Elhakim et al [28]. Administration of GAE simultaneously with IMI modifies the release of some neurotransmitters particularly GABA [29].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, some reports of NNs show the different results from the present study. TMX has been shown to significantly inhibit locomotor activity [30], CTD was shown to significantly increase anxiety-like behavior [17] and the levels of 5-HT, GABA and DA have been shown to be significantly reduced by IMI administration [1]. The effects on locomotor activities, the anxiety-like behaviors and the neurotransmitters of mice were observed to vary according to the type of NNs.…”
Section: Discussionmentioning
confidence: 97%
“…Yoneda et al 6 also reported that long-term administration of dinotefuran to mice caused a dose-dependent increase in spontaneous locomotor activity. Chronic administration of IMI has been reported to cause a decrease in voluntary locomotion, an increase in resting time, and depression 3,8,9 ; since monoamines regulate brain functions such as behavior, memory, emotion, and learning, monoamine disruption may be involved in the development of those symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Their toxicity to mammals has been reported in recent years, including neurotoxicity, reproductive toxicity, and hepatotoxicity when administered to mice and rats 9,10,11−19 . There have been many reports of neurotoxicity, including increased anxiety-like behavior and changes in spontaneous locomotion [3][4][5][6][7][8][9] . In particular, Hirano et al 5 found that clothianidin (CLO), an NN, increased anxiety-like behavior even at concentrations below the no observed adverse effect level (NOAEL).…”
Section: Introductionmentioning
confidence: 99%